Combining stereolithography and replica molding: On the way to superhydrophobic polymeric devices for photovoltaics. (5th November 2017) - Credi, Caterina; Pintossi, Diego; Bianchi, Claudia L.; Levi, Marinella; Griffini, Gianmarco; Turri, Stefano
Abstract: A strategy combining stereolithography (SL) and soft-lithography for the straightforward fabrication of superhydrophobic bulk devices is reported. Microtextured masters are rapidly prototyped by SL and passivated with a perfluorosilane. Such surface treatment enables the faultless fabrication of negative microstructured polydimethylsiloxane molds ultimately utilized to obtain bulk polymeric micropatterned structures by replica molding. As illustrative proof of concept, this approach is employed in the field of photovoltaics to realize the first example of superhydrophobic luminescent solar concentrators (LSCs) showing superior self-cleaning properties. Following our strategy, a new dye-doped acrylate mixture is developed and optimized to ensure complete wetting of the hollow microstructures present on the mold. By judiciously tailoring the photoinitiator concentration and by implementing a tailored double-step UV-irradiation process, complete UV-photopolymerization is achieved despite the significant thickness of the target samples. The high fidelity replication of the original SL-printed features on the daughter replicas as well as their super water-repellency are successfully demonstrated. The performance of the resulting superhydrophobic LSCs is investigated at varying device dimensions and found to be comparable with state-of-the-art systems. This study demonstrates the potential of high-resolution SL-printing in combination with replication techniques as a versatile tool to reproducibly fabricate microstructured superhydrophobic polymeric bulk devices in a straightforward fashion. Graphical abstract: Highlights: Microstructured molds are rapidly prototyped by combining stereolithography and replica molding Surface fluorination of 3D printed masters ensures multiple fabrication of elastomeric replicas avoiding damages Microtextured superhydrophobic bulk devices are obtained by casting a new low-surface tension polymer against the molds High-performance self-cleaning luminescent solar concentrators are rapidly fabricated and up-scaled to different dimensions